Role of Religion on Knowledge, Attitude and Practices of Lactating Mothers on Infant Feeding - Oladejo T, Adepoju; Elizabeth T, Adesemoye; Isaac O, Akinyele (International Journal of Nutrition, 2019)
Infant and young child feeding (IYCF) practices directly affect the nutritional status of children under two years of age, and ultimately, impact child survival. These practices are influenced by maternal knowledge and attitudes as well as socio-demographic and cultural factors; and an understanding of such factors is important to scaling up IYCF practices. This study was designed to assess the role of religion on knowledge, attitude and infant feeding practices among Christian and Muslim lactating mothers in Ibadan North Local Government Area (LGA), Oyo State. The descriptive cross-sectional study was conducted among 320 lactating mothers in the LGA. Eight focus group discussions were carried out among Christian and Muslim lactating mothers. An adapted pre-tested questionnaire was used to collect information on socio-demographic characteristics and IYCF knowledge, attitude and practices of the respondents. Knowledge on IYCF was assessed on 14-item scale, and the scores categorised as: ˂5.60 poor, 5.60–10.88 fair, and ˃10.88 good knowledge. Attitude was assessed on 13 statements from the IOWA Infant Feeding Attitude scale with lowest and highest obtainable score of 13 and 65 respectively. A score of ˂44 was ranked as poor, and ˃44 points good. Data were analysed using descriptive statistics and one-way ANOVA. Qualitative data was analysed thematically. Mean age of respondents was 30.0±4.9 years, 55.9% were Muslims, and 63.8% had fair knowledge. There was no significant difference in fair knowledge categorisation (63.7%, 63.8%), but there existed slight difference in good (20.7%, 21.3%) and poor (15.6%, 14.9%) knowledge of the Muslim and Christian respondents respectively. Mothers with poor attitude constituted 56.0%. Muslim religion directly supports pre-lacteal feeding and duration of breastfeeding while the other indirectly supports breastfeeding. Religious practices directly and indirectly affect knowledge, attitude and practices of nursing mothers on infant feeding; hence, healthcare Professionals should pay more attention to nutrition education in religious houses using the infant and young child feeding module.
Keywords: Infant and young child feeding; Religious practices; Breastfeeding practices; Lactating mothers